MEANING OF CAREER AS A REALITY CONTRUCTION IN MICHEL FOUCAULT PERSPECTIVE - Puspita Ningrum; Ema Damayanti; Dede Abdurrakhman (JLER (Journal of Language Education Research), 2019)
Through Michel Foucault critical discourse analysis using qualitative descriptive methods. This study aims to describe aspects of the meaning of text and context simultaneously in expression. Three caricatures in the Kompas daily published on Sunday, December 2, 2018 became the object of research. The background of how the conceptual view of realism in a media contains the power and power behind these statements. The results of the analysis show that referential meanings in three caricatures have elements of language that are closely related to the environmental, social, and cultural conditions of the community that are taking place. The editorial team has not used a neutral point of view in choosing titles, news sources and news frames. News written and published impressed as a construction of reality that aims to influence and direct the perspective of society in addressing a social problem that occurs reflecting how the power of knowledge can imply subordinate people. keywords: Michel Foucault's Analysis, Caricature, Referential Meaning, Reality Construction